Photodynamic exposure of Rose-Bengal inhibits Tau aggregation and modulates cytoskeletal network in neuronal cells - Dubey, Tushar; Gorantla, Nalini Vijay; Chandrashekara, Kagepura Thammaiah; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
The intracellular Tau aggregates are known to be associated with Alzheimer's disease. The inhibition of Tau aggregation is an important strategy for screening of therapeutic molecules in Alzheimer's disease. Several classes of dyes possess a unique property of photo-excitation, which is applied as a therapeutic measure against numerous neurological dysfunctions. Rose Bengal is a Xanthene dye, which has been widely used as a photosensitizer in photodynamic therapy. The aim of this work was to study the protective role of Rose Bengal against Tau aggregation and cytoskeleton modulations. The aggregation inhibition and disaggregation potency of Rose Bengal and photo-excited Rose Bengal were observed by in-vitro fluorescence, circular dichroism, and electron microscopy. Rose Bengal and photo-excited Rose Bengal induce minimal cytotoxicity in neuronal cells. In our studies, we observed that Rose Bengal and photo-excited Rose Bengal modulate the cytoskeleton network of actin and tubulin. The immunofluorescence studies showed the increased filopodia structures after photo-excited Rose Bengal treatment. Furthermore, Rose Bengal treatment increases the connections between the cells. Rose Bengal and photo-excited Rose Bengal treatment-induced actin-rich podosome-like structures associated with cell membranes. The in-vivo studies on UAS E-14 Tau mutant Drosophila suggested that exposure to Rose Bengal and photo-excited Rose Bengal efficiency rescues the behavioural and memory deficit in flies. Thus, the overall results suggest that Rose Bengal could have a therapeutic potency against Tau aggregation.